THE INFLUENCE OF CONSUMER BEHAVIOR ON PURCHASE DECISION OF INDOMIE INSTANT NOODLE PRODUCTS AT PT. INDOFOOD SUCCESS MAKMUR TBK : CASE STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS, MAKSSAR STATE UNIVERSITY - Zulfadli S; Parawansa, Dian Anggraece Sigit; Mustafa, Fahrina (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
An understanding of consumer behavior is very much needed at this time, where the development of fast food is so rapid and fast that the intensity of competition is getting higher, this is important for marketers if they want to continue to be accepted by their consumers. This study aims to: 1) To find out whether cultural, social, personal, and psychological factors influence the buying decision of Indomie instant noodles. 2) To find out which variable has the dominant influence on purchasing decisions for Indomie product instant noodles. This study uses qualitative research. The population used in this study were 100 respondents, students of the Faculty of Economics, and data collection in the form of observations, interviews, and questionnaires. Using the SPSS 21 for windows program to test the validity, reliability and multiple linear regression analysis. From the results of the analysis it was found that cultural factor variables, had an insignificant (significant) influence on purchasing decisions of Indomie instant noodles while social, personal, and cultural factors had a significant effect on purchasing decisions of Indomie instant noodles and psychological variables had a dominant influence on purchasing decisions of Indomie instant noodles.